Tracking development assistance for health from China, 2007–2017. Issue 5 (October 2019) - Micah, Angela E; Zhao, Yingxi; Chen, Catherine S; Zlavog, Bianca S.; Tsakalos, Golsum; Chapin, Abigail; Gloyd, Stephen; Jonas, Jost; Lee, Paul H; Liu, Shiwei; Ng, Man Tat Alexander; Phillips, Michael R; et al.
Abstract : Introduction: In recent years, China has increased its international engagement in health. Nonetheless, the lack of data on contributions has limited efforts to examine contributions from China. Existing estimates that track development assistance for health (DAH) from China have relied primarily on one dataset. Furthermore, little is known about the disbursing agencies especially the multilaterals through which contributions are disbursed and how these are changing across time. In this study, we generated estimates of DAH from China from 2007 through 2017 and disaggregated those estimates by disbursing agency and health focus area. Methods: We identified the major government agencies providing DAH. To estimate DAH provided by each agency, we leveraged publicly available development assistance data in government agencies' budgets and financial accounts, as well as revenue statements from key international development agencies such as the WHO. We reported trends in DAH from China, disaggregated contributions by disbursing bilateral and multilateral agencies, and compared DAH from China with other traditional donors. We also compared these estimates with existing estimates. Results: DAH provided by China grew dramatically, from US323.1 million in 2007 to 652.3 million in 2017. During this period, 91.8% of DAH from China was disbursed through its bilateral agencies, including the Ministry of Commerce (3.7 billion, 64.1%) and the National Health Commission (917.1 million, 16.1%); the other 8.2% was disbursed through multilateral agencies including the WHO (236.5 million, 4.1%) and the World Bank (123.1 million, 2.2%). Relative to its level of economic development, China provided substantially more DAH than would be expected. However, relative to population size and government spending, China's contributions are modest. Conclusion: In the current context of plateauing in the growth rate of DAH contributions, China has the potential to contribute to future global health financing, especially financing for health system strengthening.